Prevalence of Ocular Demodex Infestation in Children: An Epidemiological Survey in South China. Issue 1 (January 2021) - Zhang, Nuan; Liu, Yan; Wen, Kuiyao; Jin, Ling; Chen, Chuan; Chen, Qianyun; Zeng, Yangfa; Liang, Lingyi
Abstract : Objectives: To investigate the prevalence of and risk factors for Demodex mite infestation of the eyelashes in Chinese children. Methods: A total of 1, 575 children were surveyed from June 2017 to January 2019 and stratified into two age groups: 3 to 6 and 7 to 14 years. All subjects underwent routine eye examination and lash epilation for Demodex mite identification and counting using microscopy. Demographic data and lifestyle habits were also recorded. Results: Demodex mites were detected in 189 of 1, 575 (12.0%) children, including Demodex folliculorum ( D. folliculorum ) in 180 (11.4%), Demodex brevis ( D. brevis ) in 11 (0.7%), and both mites in 2 (0.1%). The median number of D . folliculorum mites was 1 (interquartile range [IQR], 1–2) and that of D . brevis was 1 (IQR, 1–1). Children with Demodex infestation did not exhibit more ocular discomfort than those without (21.2% vs. 23.1%; P =0.56). However, lash abnormalities, including trichiasis, cylindrical dandruff, or scaly discharge at the lash root, were more prevalent in children with Demodex infestation (24.9% vs. 12.8%; P <0.001) and in the 7 to 14-year subgroup (33.7% vs. 12.8%; P <0.001). Multiple logistic regression revealed that autumn–winter was associated with a higher detection rate of Demodex infestation (all P <0.05). In the 3-6-year subgroup, children residing in rural regions exhibited a higher prevalence of Demodex infestation ( P =0.03). Conclusions: Ocular Demodex infestation, with a low Demodex mite count, was found in healthy Chinese children aged 3 to 14 years.